Identification of prognostic RNA editing profiles for clear cell renal carcinoma - Chen, Weihong; Li, Shaobin; Huang, Dongqin; Su, Yuchao; Wang, Jing; Liang, Zhiru (Frontiers in Medicine, 2024)
Objective: Clear cell renal cell carcinoma (ccRCC) is the most common type of renal cancer and currently lacks effective biomarkers. This research aims to analyze and identify RNA editing profile associated with ccRCC prognosis through bioinformatics and in vitro experiments.Methods: Transcriptome data and clinical information for ccRCC were retrieved from the TCGA database, and RNA editing files were obtained from the Synapse database. Prognostic models were screened, developed, and assessed using consistency index analysis and independent prognostic analysis, etc. Internal validation models were also constructed for further evaluation. Differential genes were investigated using GO, KEGG, and GSEA enrichment analyses.Furthermore, qPCR was performed to determine gene expression in human renal tubular epithelial cells HK-2 and ccRCC cells A-498, 786-O, and Caki-2.Results: An RNA editing-based risk score, that effectively distinguishes between high and low-risk populations, has been identified.